2022
DOI: 10.1155/2022/8326591
|View full text |Cite
|
Sign up to set email alerts
|

M2-Macrophage-Derived Exosomes Promote Meningioma Progression through TGF-β Signaling Pathway

Abstract: Tumor-associated macrophages (TAMs) have been shown to be an essential component of the tumor microenvironment and facilitate the proliferation and invasion of a variety of malignancies. However, the contribution of TAMs to meningioma progression has not been characterized in detail. In this study, we aimed to discover a novel regulatory pathway by which exosome-mediated M2-polarized macrophages participate in meningioma tumorigenesis and progression. Methods. First, the distribution and functional phenotype o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…When these were compared against the MNG EV proteins we identified, a total of 11 common proteins were identified (PGK1, ALDOA, ANAXA1, HSPB1, PFN1, PKM, S100A11, SPTBN1, SPTAN1, PLEC and TF). Our study not only confirms the presence of proteins previously identified in MNG EVs (4,(7)(8)(9)(10)(11)(12)25), but also identified novel proteins that have not been previously reported in association with MNG EVs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…When these were compared against the MNG EV proteins we identified, a total of 11 common proteins were identified (PGK1, ALDOA, ANAXA1, HSPB1, PFN1, PKM, S100A11, SPTBN1, SPTAN1, PLEC and TF). Our study not only confirms the presence of proteins previously identified in MNG EVs (4,(7)(8)(9)(10)(11)(12)25), but also identified novel proteins that have not been previously reported in association with MNG EVs.…”
Section: Discussionsupporting
confidence: 89%
“…Differential expression analysis was utilized to reveal the relative abundance of proteins that were enriched in the EVs compared to the tumour tissue. Our study not only confirms the presence of proteins previously identified in GBM EVs from various sources (including CUSA washings, cell lines, and plasma) (4,(7)(8)(9)(10)(11)(12)25), but also crucially identified novel proteins that have not been reported before in association with GBM EVs before including proteins associated with solute carrier transporters and fatty acid transport. Recently it has been shown that solute carrier family members can promote the progression of GBM by activating the PI3-AKT signalling pathway (44).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…According to recent studies, circulating miRNAs such as miRNA 497 and 219 inside the exosomes have the potential to be used as cancer biomarkers in various tumors including meningiomas [ 194 ]. In another study, M2 macrophage-derived exosomes were found to stimulate meningioma progression through the TGF-β signaling pathway [ 195 ]. Fibulin-2 was observed as another marker for differentiating grade II and grade I meningiomas [ 196 ].…”
Section: Targeting Therapiesmentioning
confidence: 99%
“…Macrophages are one of the most prevalent types of immune cells in the TME [ 6 ]. They have two distinct functional subtypes: M1, which inhibits tumor growth by producing pro-inflammatory cytokines [ 7 , 8 ], and M2, which promotes tumor growth by producing anti-inflammatory cytokines [ 9 , 10 ]. The majority of tumor-associated macrophages (TAMs) have characteristics of M2-polarized cells [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%